Summary of the 2nd International Workshop on Environmental, Safety and Economic Aspects of Fusion Power. (4th July 2018) - Wu, Y.; Chen, Z.; Meng, Z.; Hu, L.; Gonzalez de Vicente, S.M.; Merrill, B.; Panayotov, D.; Zucchetti, M.; Kolbasov, B.; van Houtte, D.; Bustreo, C.; Kim, Y.; et al.
Abstract: The 2nd International Workshop on Environmental, Safety and Economic Aspects of Fusion Power (ESEFP) was held on 23 September 2017 in Kyoto, Japan. The workshop was initiated by the International Energy Agency Technology Collaboration Program on ESEFP. The workshop was well attended with approximately forty participants representing fifteen institutions in eight countries. The presentations covered safety issues and environmental impacts, availability improvement and risk control and socio-economic aspects of fusion power. Quantitative safety assessment of fusion reactors was discussed in depth with the consensus output presented as a plenary presentation at the 13th International Symposium on Fusion Nuclear Technology (ISFNT-13). The next workshop is planned to be held in conjunction with the ISFNT-14 in 2019.